Tomato tolerance and purple nutsedge control with sulfuryl fluoride mixes. (12th December 2021) - Yu, Jialin; Freeman, Joshua H.; Boyd, Nathan S.
Abstract: Sulfuryl fluoride (SF) is currently used as a fumigant for control of drywood termites and insects in building structures, vehicles, wood products, postharvest commodities, and food processing facilities. This research investigated the feasibility of using SF as a preplant soil fumigant for purple nutsedge control in plastic-mulched tomato production. SF treatments included SF injected through drip tapes or SF injected through drip tapes a few hours following shank injection of chloropicrin (Pic). Results revealed that SF alone at 224, 336, or 448 kg ha −1 was generally less effective compared with when it was applied in conjunction with Pic at 168 kg ha −1 . SF alone provided inconsistent control of purple nutsedge. In contrast, SF + Pic was as efficacious or more efficacious on purple nutsedge than the industry standards, including 1, 3-dichloropropene (1, 3-D) plus Pic and metam potassium. None of the fumigant treatments visually injured tomato plants, stunted growth, or adversely affected tomato yield. In one of the four tomato seasons, tomato plants growing in plots fumigated with SF + Pic resulted in taller tomato plants and higher markable yields. Results indicate that soil fumigation with SF + Pic is safe on plastic-mulched tomato and effectively controls purple nutsedge.